Integrating 21st Century Skills into Higher Education Curricula: Challenges and Opportunities - Ridwan; Oswald Timothy Edward (Siber Nusantara of Education and Sport Review, 2024)
This paper delves into the incorporation of 21st-century skills within higher education curricula, emphasizing the urgent need for educational systems to adapt to modern demands. It addresses the integration of essential skills such as critical thinking, collaboration, digital literacy, and problem-solving into academic programs. The research utilizes a comprehensive review of literature and examines case studies from various institutions that have implemented these skills into their curricula. Results show that while the importance of these skills is widely acknowledged, the actual implementation varies significantly among institutions. The study concludes that a well-structured curriculum design, involving active stakeholder participation and regular evaluations, is crucial for successful integration.